Copper and cadmium impair sperm performance, fertilization and hatching of oocytes from Amazonian fish Colossoma macropomum - Pinto, Gustavo Lemes; da Silva Castro, Jonatas; Val, Adalberto Luis (Chemosphere, 2020)
The contamination of aquatic environments by transition metals can have a direct influence on the reproductive process of several organisms in the aquatic biota. This study aimed to evaluate the effect of cadmium and copper on the sperm of tambaqui (Colossoma macropomum). Male (n = 4) and female (n = 4) specimens of C. macropomum were induced to spermiation and ovulation, with sperm being activated in the following media: 0; 0.6; 1.2 and 1.8 mg/L of cadmium (CdCl2) and 0; 0.4; 0.8 and 1.2 mg/L of copper (CuCl2). Sperm quality was assessed through time (s) and motility rate (%), superoxide dismutase (SOD) and glutathione S-transferase (GST) activities, lipoperoxidation levels (LPO), and morphological characteristics. In parallel, the effects of these metals on the rate of fertilization and hatching of the oocytes were evaluated. The duration and motility rate of sperm were longer in the control treatment, 85.67 ± 11.01 s; 90 ± 0.01%, and progressively decreased to 44.67 ± 4.16 s and 60 ± 5%, respectively, in concentrations of 1.8 mg/L (44.67 ± 4.16 s; 60 ± 5%) of CdCl2 and to 65.67 ± 3.30 s; 70 ± 5%, respectively, in concentrations of 0.8 mg/L of CuCl2. We observed an increase in the activity of the SOD enzyme in sperm cells exposed to 1.2 mg/L of CdCl2. The LPO levels were increased significantly in sperm cells exposed to 1.2 and 1.8 mg/L of CdCl2 and 0.8 mg/L of CuCl2. Fertilization and hatching were severely impaired in the presence of Cd and Cu. These data indicate that environments contaminated with cadmium and copper harm the gametes of C. macropomum. © 2020 Elsevier Ltd
Keywords: Aquatic Organisms; Cadmium; Cadmium chloride; Chlorine Compounds; Copper; Copper compounds; Enzyme Activity; Nitrogen Compounds; Aquatic biota; Aquatic Environments; Control Treatments; Glutathione S-transferases; Lipoperoxidation; Morphological characteristic; Sperm quality; Superoxide Dismutases; Uranium compounds